Influence Creativity and Social Media on the Success of Talang Bandung Culinary Village in Districts Ogan Commuting Ulu - Rini Apriyani; Robby Juniansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The formulation of the problem in this study is whether creativity and social media affect the success of the culinary village in the Ogan Komeringbulu Regency. The purpose of this study is to determine the effect of creativity and social media on the success of the Talang Bandung Culinary Village in Ogan Komering Ulu Regency. The method used in this research is descriptive. Based on the results of data processing, the multiple linear regression equation is as follows: Y = 2,200 + 0.168X1 + 0.675X2. Based on the R-value of the correlation coefficient, it can be seen that r = 0.870 is in the interval 0.80 - 0.1000, meaning that the relationship between Creativity (X1) and Social Media (X2) on Business Success (Y) in Culinary Villages is very strong. The value of the coefficient of determination R square is 0.756, this shows that the influence of the variables Creativity (X1) and Social Media (X2) on Business Success (Y) is 75.6% while the remaining 24.4% is influenced by other factors not examined in this study this research. Based on the count for the Creativity variable (X1) count = 0.890 and obtained stable = 2.042 so the value obtained is 0.890 <2.042 or count < table, the decision Ho is accepted Ha is rejected so there is no influence between the Creativity variable (X1) on Business Success (Y). Then for the Social Media variable (X2) count = 3.917 and table 2.042 so the value obtained is 3.917>2.042 or tcount>ttable, the decision is Ho rejected, Ha is accepted, so there is an influence of Social Media (X2) on Business Success (Y). Based on the Fount value, which is 46.561, and Table 3.32 is obtained, it becomes 46.561 > 3.10. So the decision was rejected Ho Ha accepted. So there is the influence of Creativity (X1) and Social Media (X2) on Business Success (Y) in the Culinary Village of Talang Bandung.